Kaum Marginal Dilarang Sakit: Marginalisasi Masyarakat Miskin Atas Hak Kesehatan di Kota Surabaya - Sultoni Fikri (CV. Era Digital Nusantara, 2023)
This research aims to describe the marginalized poor in the form of health rights. Health politics is very important by making policies in the health sector because health is a basic need that must be met. Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS/Social Security Agency of Health) is an instrument to carry out development in the health sector. Based on the issues raised, researchers used Janice Perlman’s marginal theory to analyze. The method used in this research is qualitative-descriptive analysis of data obtained through interviews, observations, and literature review. The results of the analysis found that there are still poor people who are marginalized for health rights. This is because in the implementation of the Health Social Security Agency program there is still discrimination in accessing health services and there are still poor people who do not have health insurance to access existing health services.